Communicating Nutrition, Food, and Health Information: New Paradigms Revisited. Issue 2 (6th March 2023) - Rowe, Sylvia; Alexander, Nick
Abstract : In the several years since we last proposed in-depth analysis and guidance for health and nutrition communicators, in light of the evolving information environment, much has changed—mostly for the worse, for the more problematic. The communication landscape has become more challenging, public trust in health institutions seems to have experienced further shrinkage, and some of the old rules for disseminating consensus scientific information may need updating. In this article, we analyze recent events/conditions in the ongoing metamorphosis of the communication environment in the cyber age. Included are some observations from a 2022 National Academies of Sciences, Engineering, and Medicine workshop on best practices for nutrition communication, analysis of misinformation concerns, the effect of social media on information delivery, and some updated guidance for communicators.